The Effect of Applying Eggshell-Based Liquid Fertilizer on The Growth of Leek Plants (Allium fistulosum L.) - Sulistiyanti, Eva; Mumtaz, Hana; Ilham, Muhammad Nur; Farid, Mumtazah Imtiyaz; Azzahra, Putri Nazma; Qudsi, Qisthina Hunafa; Yulianty, Nurfitri; Suwandi, Tri (Universitas Pendidikan Indonesia and Konsorsium Biologi Indonesia, 2025)
Eggshell-based liquid organic fertilizer (LOF) is a sustainable nutrient source rich in nitrogen (N), phosphorus (P), and potassium (K), essential for plant growth. This study investigated the effects of eggshell LOF on the growth of leek plants (Allium fistulosum L.) using a Completely Randomized Design (CRD) with five concentration treatments: 0% (P0, control), 5% (P1), 10% (P2), 15% (P3), and 20% (P4), each replicated three times. The experiment was conducted in Kel. Isola, Kec. Sukasari, Bandung City, Indonesia, during December 2022. Plant height was measured every three days for two weeks as the primary growth parameter. Results demonstrated significant differences (*p* 0.05) among treatments, with the 20% LOF concentration (P4) yielding the highest average plant height (22.7 cm). In contrast, the 5% LOF group (P1) showed no growth, indicating plant mortality. A positive correlation was observed between LOF concentration and plant height, confirming that higher nutrient availability directly enhances leek growth. These findings highlight the efficacy of eggshell LOF, particularly at 20% concentration, as a viable organic fertilizer for improving Allium fistulosum productivity. Further research is recommended to explore optimal concentrations beyond 20% and assess long-term soil health impacts.